If it's not what You are looking for type in the equation solver your own equation and let us solve it.
83=f/10--77
We simplify the equation to the form, which is simple to understand
83=f/10+77
We move all terms containing f to the left and all other terms to the right.
-0.1f=+77-83
We simplify left and right side of the equation.
-0.1f=-6
We divide both sides of the equation by -00.1 to get f.
f=60
| 12b+35=76+11b | | a^2-16a+48=0 | | 2(2y)-3y=y | | 3x+9+4+4x+8x+5=90 | | 2x-50=-8x | | 4-3(2y-6)= | | 2(n-12)=2 | | 15-4v=-1 | | 12(4)-2y=12 | | 10K=9K+6 | | -10=18x-28 | | 16+r^2-8r= | | -3b=126 | | 4p--2=14 | | 12(2)-2y=12 | | 11x+1=3x+7 | | 12(0)-2y=12 | | 4+b^2-4b= | | 16-q=-3 | | 2P-5=2P | | 2(s+18)=0 | | 14=z/2--12 | | 12(-2)-2y=12 | | 14=z/2--13 | | 6x+7=-5+3x+18 | | 84+2x=178 | | 12(-4)-2y=12 | | 24.0/0.05 | | 16+v^2-8v= | | 8x=6x-(11-2x) | | -3(t-1)+6t=7t-2 | | y=-28+18 |